A The relationship between nutritional status and the incidence of premenstrual syndrome (PMS) in adolescent girls - Sherly Pratiwi Apriliani; Istinengtiyas Tirta Suminar; Triani Rahmadewi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Adolescent girls are a group of women aged 10-19 who are transitioning from childhood to adulthood. During this developmental phase, complex physical, psychological, and social changes occur, including the onset of the menstrual cycle, which is often accompanied by various complaints. One common complaint is Premenstrual Syndrome (PMS). PMS is a health condition often experienced by adolescent girls during puberty. Purpose: To determine the relationship between nutritional status and the incidence of premenstrual syndrome (PMS) in adolescent girls. Method: This quantitative study used a descriptive analytical approach and a cross-sectional design. This study was conducted at SMPN 4 Gamping. Sample selection was determined using a purposive sampling technique with the Slovin formula. Data analysis was performed using univariate and bivariate analysis with the Somers'd test at a significance level (α) of 0.05. Results: The analysis using the Somers' d test showed a coefficient value of -0.279 with a significance value of p = 0.034. Since the p value <0.05 indicates a significant relationship between nutritional status and the incidence of Premenstrual Syndrome (PMS) in adolescent girls, the coefficient value of -0.279 indicates a negative relationship with a weak correlation. Conclusion: There is a significant relationship between nutritional status and the incidence of Premenstrual Syndrome (PMS) in adolescent girls.